Design of Noise Insulator for Metal Stamping Operation in Manufacturing Sector - Halim, Isa; Syed Mohamed, Muhammad Syafiq; Jin, Lee Song; Azani, Akmal Hafiz (International Journal of Integrated Engineering, 2019)
Metal stamping is one of the processes involved in metal manufacturing in which dies are used to cut or form flat metal sheets into desired shapes. Consequently, noise is produced from the process. Prolonged exposure to the noise can lead to the health problems, low productivity and low performance of workers. The aim of this study is to design a noise insulator for noise level reduction in a metal stamping operation. This study applied workplace observation, questionnaire survey and noise mapping at the metal stamping workstations.  A prototype design of noise insulator was developed through brainstorming among the metal stamping workers, questionnaire survey and morphological chart. Recycled papers and coconut fibers were used as materials of the noise insulator. Noise level assessment was conducted to determine the effectiveness of the developed noise insulator. The noise levels have been effectively reduced to 70.3 dBA by 17.2%. This study concluded that application of materials such as recycled papers and coconut fibers in making of noise insulator was able to reduce noise levels in metal stamping operation. This study suggests that the real fabrication and application should be implemented in the metal stamping operation to reduce the risk of noise exposure to the workers.